ASSESSMENT AND EVALUATION BEING USED IN CLASSROOMS BY FOUNDATION OF LISTENING LECTURER - Iyan Irdiyansyah; Gusnadi Gusnadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2018)
ABSTRACTDetermining the implementation of the assessment and evaluation being used in Foundation of Listening Subject Lecturer become the objective of this study. It is conducted to the Foundation of Listening Subject lecturer in first semester of English Education Study Program, School of Education, Pakuan University, Bogor Indonesia. Qualitative approach and Descriptive are used as method. Observation, questionnaire and interview are utilized for data collection. The findings of the study are that most of the lecturer applied multiple choice question taken from TOEFL test book to test students knowledge, while the classroom performance is assessed by performance test.Keywords: Assessment, Evaluation, Foundation of Listening